Enhancing capacity for resilient agriculture planning and programming in Kenya - Kimani, Owen Samuel; Templer, Noel Anyuka; Kinyua, Ivy Wambui; Jalango, Dorcas Anyango; Mutui, Edith Judith; Mwongera Mugambi, Caroline Njeri (2022)
The Alliance of Bioversity International and CIAT has been working on several projects led by Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) in six countries—Senegal, Mali, Ghana, Ethiopia, Kenya, and Zambia. These actions are to show that innovation is a necessary but insufficient factor in transforming food systems under climate change. Ahead of COP27, AICCRA developed a diagnostic framework and checklist that enables African policymakers to set policy priorities for the transformation they seek of national and regional food systems under climate change.